2001
DOI: 10.1177/014920630102700102
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the relationship of governance mechanisms to performance

Abstract: The purpose of this paper is to draw together the many different facets of corporate governance that have been examined in the extensive literature in both strategic management and finance. In particular, we are interested in the relationship between the typical agency theory constructs of monitoring, incentives and ownership structure, with financial performance. First, we catalog this large body of work to see where there are still unanswered questions. We find that previous work has generally focused on exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
258
3
30

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(310 citation statements)
references
References 54 publications
19
258
3
30
Order By: Relevance
“…Board of directors is designated for the purpose of ensuring the alignment of the fi rm activities with its specifi ed objectives. The board has the duty for making sure that the top managers are behaving in a way that will provide the optimal value for shareholders (Coles et al 2001). …”
Section: Hypothesis 1 Mfis Whose Manager Receives a Fi Xed Salary Wimentioning
confidence: 99%
“…Board of directors is designated for the purpose of ensuring the alignment of the fi rm activities with its specifi ed objectives. The board has the duty for making sure that the top managers are behaving in a way that will provide the optimal value for shareholders (Coles et al 2001). …”
Section: Hypothesis 1 Mfis Whose Manager Receives a Fi Xed Salary Wimentioning
confidence: 99%
“…The findings of most of the studies indicate insignificant effects (Rechner and Dalton, 1989;Dalton, 1992, 1993;Baliga et al, 1996). In some studies, it was found out that CEO duality have a positive effect on organizational performance (Daily and Dalton, 1994), whereas some other studies indicate negative effect (Rechner and Dalton, 1991;Coles, McWilliams, and Sen, 2001). Johnson, Daily and Ellstrand (1996) define inside directors as the directors who are also officers of the organization, and outside directors as all non-management members of the board.…”
Section: Ceo Dualitymentioning
confidence: 96%
“…Clearly, the board of directors plays a very significant role in maximizing shareholders' wealth via exercising control over top management (Kose and Senbet, 1998). As a corporate governance mechanism, the board members are also to ensure adequate returns for shareholders (Vafeas, 1999;Weir and McKnight, 2001;Coles et al, 2001). The general principles in the Malaysian Code of Corporate Governance in 2000 cover the aspects of board structure, board size and independent board of directors.…”
Section: Top Management Teams (Tmts) and Board Of Directors (Bods)mentioning
confidence: 99%